Discrimination of Rhythmic Pattern at 4 Months and Language Performance at 5 Years: A Longitudinal Analysis of Data From German‐Learning Children. Issue 2 (September 2014) - Höhle, Barbara; Pauen, Sabina; Hesse, Volker; Weissenborn, Jürgen; Molnar, Monika; Sebastian‐Galles, Nuria
<x xml:space="preserve">Abstract</x> In this article we report on early rhythmic discrimination performance of children who participated in a longitudinal study following children from birth to their 6th year of life. Thirty‐four children including 8 children with a family risk for developmental language impairment were tested on the discrimination of trochaic and iambic disyllabic sequences when they were 4 months old. At 5 years of age, standardized measures on language performance (SETK3–5) and nonverbal intelligence (SON‐R) were obtained. Overall, evidence of discrimination of the rhythmic patterns was found only for children without a family risk. The performance in early rhythmic discrimination correlated with the later outcomes in SETK3–5 subtests on sentence comprehension and morphological skills, but not with subtests related to memory performance nor with nonverbal intelligence. Our results suggest that indicators of language development can be discovered as early as 4 months of age, and seem to correlate with later outcomes in rather specific language skills.